Waste eliminated by waste under COVID-19 pandemic: Mixed plastic waste derived N, O-rich porous carbon nano-coral reefs for chlorophenol pollutants efficient capture. Issue 6 (December 2021) - Li, Xin; Shan, Yuling; Zhang, Xiaolei; Zhao, Shilei; Yu, Wenlong; Liu, Yibin; Shang, Hongrui; Tang, Peilong; Wang, Shusen; Ding, Junwei
Abstract: Both increasing emission of chlorophenol chemicals and plastic waste pollution are severe global environmental challenges, which is worth being explored to respond with a "waste eliminated by waste" coupling treatment strategy. Herein, we propose a one-step recyclable nano-MgO template strategy to prepare in-situ N, O-doped novel porous carbon coral reefs (PCNCR) directly derived from the mixture of real waste PET and melamine formaldehyde resin. The template precursor can be conveniently recycled by facile acetic acid pickling, vacuum evaporation and drying, and the whole preparing process does not involve any toxic solvents, massive consumption of pore-forming agents, or discharge of salty wastewater. The obtained PCNCRs have hierarchical porous structures and abundant N, O-doped species, and the textural parameters can be modulation linearly by varying the mass ratio of magnesium acetate to mixed waste plastics. The optimized PCNCR-1.25 exhibited remarkable adsorption capacity for chlorophenol contaminants (777.5 mg/g for 4-Chloro-3, 5-dimethylphenol, PCMX and 538.74 mg/g for 4-Chloro-3-methylphenol, PCMC) in aqueous solution. Adsorption isotherm fitting studies revealed chlorophenol contaminants tended to be rapidly adsorbed on the PCNCR surface in the form of monolayer. And the system reached adsorption equilibrium at about 15 min, which was described by linear driving force model. Reusability test verified that PCNCR-1.25 had excellent adsorption stability for chlorophenol in continuous adsorption-regeneration cycles. DFT calculation illustrated the enhancement of chlorophenol adsorption by heteroatom species, especially nitrogen dopants. This work highlighted a low-cost and sustainable approach to defuse the dual environmental threat of chlorophenol emissions and plastic waste pollution simultaneously. Graphical Abstract: ga1 Highlights: Porous carbon nano-coral reefs (PCNCRs) derived from plastic waste were prepared. A facile one-step recyclable MgO template strategy was used for PCNCR synthesis. PCNCRs were used for chlorophenol removal with remarkable adsorption capacity. N-species on carbon surface enhanced the adsorption of chlorophenols.